Analisis Inovasi Layanan Anak ”Kurenah Storytelling” Terhadap Peningkatan Kunjungan Pemustaka Di Perpustakaan Daerah Kota Padang Panjang - Rika Jufriazia Manita; Fega Nurhidayati (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2022)
The main problem in this thesis is the interest of visiting users in children's services at the Padang Panjang City Library. The purpose of this study was to determine whether the innovation of children's services